Myc signaling via the ARF tumor suppressor regulates p53-dependent apoptosis and immortalization - Zindy, Frederique (Cold Spring Harbor Laboratory Press, 1998)
Establishment of primary mouse embryo fibroblasts (MEFs) as continuously growing cell lines is normally accompanied by loss of the p53 or p19(ARF) tumor suppressors, which act in a common biochemical pathway. myc rapidly activates ARF and p53 gene expression in primary MEFs and triggers replicative crisis by inducing apoptosis. MEFs that survive myc overexpression sustain p53 mutation or ARF loss during the process of establishment and become immortal. MEFs lacking ARF or p53 exhibit an attenuated apoptotic response to myc ab initio and rapidly give rise to cell lines that proliferate in chemically defined medium lacking serum. Therefore, ARF regulates a p53-dependent checkpoint that safeguards cells against hyperproliferative, oncogenic signals.